Good governance in the health sector of Malawi - Kaisi, Sherrif Abobakar; Quddus, S M Abdul (IIUM Press, 2017)
Good governance is a term used to denote the structures and processes by which the system of a country is regulated, directed and controlled; it encompasses the obligations of stewardship. The purpose of this research based book is to examine and explore how health care services are delivered in Malawi health care systems with particular focus on the Queen Elizabeth Central Hospital (QECH) in Blantyre Malawi from the good governance perspective. Data for this book project were elicited through interviews and survey and the procedure employed was triangulation. A case study method was employed which involved breaking the interviews into themes, comparing the participants’ perception on good governance in the healthcare sector and determining the commonality among those perceptions. Some of the significant statements and themes generated during the course of qualitative data analysis for both the service providers and service receivers included vision and mission present but obscure; views shared not considered; disparity in treatment due to social standing; equal treatment for all despite race, religion and gender; limited freedom of expression; patients’ relationship with staffs not wholly amicable; hospital service ineffective due to the lack of facilities; lack of accountability and responsiveness; poor information dissemination system and hospital staff ethically upright.